4 axis machining simulation routines via application programming interface (API) in cam systems - Mohamad Hafiz, Mohamad (2021)
Most of the Computer-Aided Manufacturing (CAM) systems were built-in with the simulation tools for validation purposes. In machining process planning, simulation has become an important element to achieve reliable output and obtain efficient result. Proper selection of optimum machining parameters will allow effective cutting operation with minimum time and good product quality. However, the simulation tasks in CAM system can become inefficient especially for the repeating routines that required various possibility input to the analysis. Manual human interventions are still needed for machining simulation setup. The objective of this research is to investigate the implementation of programming interface in CAM systems to handle simulation routines. The research is specifically focus on the correlation of several cutting approaches towards machining efficiency particularly in 4 axis milling machining. The applications namely as RoughSimulCAM and FinishSimulCAM were developed to assist the simulation routines in CAM interface. Basically, the development involves translating the simulation instructions in CAM into programming language. From this point, the codes are modified, enhanced and customized to assist the simulation routines. The functions of the developed applications are to simulate series of machining operations based on variable input data and generate optimum parameters for cutting processes. These applications are programmed in Visual Basic 10 and integrated within NX CAM 10 system. The applications work on two different stages of cutting which are roughing and finishing operations. The cutting parameter evaluated in roughing operations is cutting orientation, while in finishing operation, the axial and radial depth-of-cut is studied. RoughSimulCAM analyzes roughing operation through the manipulation of different cutting orientation and generate estimated volume removed. Orientations set with highest volume remove is selected as optimum parameter to execute roughing operations. FinishSimulCAM works to establish optimum correlation between axial depth-of-cut (ADOC) and radial depth-of-cut (RDOC). A set of ADOC and RDOC with highest volume remove will be proposed at the end of the simulation. This parameter is highly depending on the geometrical features presented on machined part. Series of machining operations were carried out in 4 axis CNC milling machine setup to validate the program. This research is part of an attempt to establish efficient method in performing the simulation routines for CNC machining. Ultimately, the method proposed in this research manages to improve overall machining simulation processing times up to 77.3%, which is from 22.50 min to 5.11 min per operation. In terms of surface roughness performances, overall results achieve for each simulation are below than 1.0 µm, which is acceptable for finishing operation with manual polishing. The implications can be perceived from this study is capable to minimized of process planning tasks, expanded the CADCAM ability to simulate various cutting approaches and managed to obtain acceptable quality of machined parts.